Consequences of disclosing clinical trial results: Evidence from the food and drug administration amendments act - BORVEAU, Thomas (Institutional Knowledge at Singapore Management University, 2020)
We examine how the U.S. Food and Drug Administration Amendments Act (FDAAA) of 2007, which requires additional disclosures regarding clinical trial results, impacts information asymmetry between the disclosing pharmaceutical firm and capital market participants, the general public, academics, and practitioners. We document a reduction in information asymmetry in capital markets. We also document an increase in adverse event and product problem complaint reports filed against the pharmaceutical firms to the FDA and a higher number of drug and medical device recalls for affected firms after the FDAAA enactment. Finally, cross-sectional analyses suggest that the increase in FDA complaint reports and recalls after the FDAAA enactment was more prominent in firms with a higher bid-ask spread decrease. Taken together, our results suggest that the FDAAA has some benefits for both investors and consumers.